2015
DOI: 10.1038/srep08139
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Peptidomimetic Modulators of Aβ Toxicity in Alzheimer's Disease

Abstract: Alzheimer's disease is one of the devastating illnesses mankind is facing in the 21st century. The main pathogenic event in Alzheimer's disease is believed to be the aggregation of the β-amyloid (Aβ) peptides into toxic aggregates. Molecules that interfere with this process may act as therapeutic agents for the treatment of the disease. Use of recognition unit based peptidomimetics as inhibitors are a promising approach, as they exhibit greater protease stability compared to natural peptides. Here, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 49 publications
(60 reference statements)
1
83
0
Order By: Relevance
“…89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates. 91 The efficacy of 5 and 6 was studied in a yeast cell model displaying Ab42 toxicity and the peptidomimetic (5 and 6) succeeded in rescuing the yeast cells from Ab42 toxicity by clearing the Ab aggregates from the cell through upregulation of autophagy. To enhance the binding affinities of inhibitors we incorporated multiple hydrogen bond donor-acceptor moieties at the N-terminal and modified the backbone by introducing N-methylglycine units (Sr = sarcosine) at alternate positions of the recognition unit to retain its recognition properties and also to enhance its blood serum stability (5: thymine-SrL(Sr)F(Sr)A-NH 2 , 6: thymine-K(Sr)V(Sr)F(Sr)-NH 2 ).…”
Section: View Article Onlinementioning
confidence: 99%
“…89 Mandal et al introduced ortho-aminobenzoic acid (Ant) in a known Ab inhibitor to obtain [Ac-L(Ant)FFD-NH 2 ] (4) as a modulator for both inhibition and dissolution of Ab40 aggregates. 91 The efficacy of 5 and 6 was studied in a yeast cell model displaying Ab42 toxicity and the peptidomimetic (5 and 6) succeeded in rescuing the yeast cells from Ab42 toxicity by clearing the Ab aggregates from the cell through upregulation of autophagy. To enhance the binding affinities of inhibitors we incorporated multiple hydrogen bond donor-acceptor moieties at the N-terminal and modified the backbone by introducing N-methylglycine units (Sr = sarcosine) at alternate positions of the recognition unit to retain its recognition properties and also to enhance its blood serum stability (5: thymine-SrL(Sr)F(Sr)A-NH 2 , 6: thymine-K(Sr)V(Sr)F(Sr)-NH 2 ).…”
Section: View Article Onlinementioning
confidence: 99%
“…One of the straightforward approaches to target amyloid-linked diseases and its associated medical complication is to find potential inhibitors against the onset of amyloid aggregation of proteins. Candidates ranging from single amino acids (Kar and Kishore 2007;Shiraki et al 2002;Ghosh et al 2009) and natural products (Stefani and Rigacci 2013) to selected peptides (Etienne et al 2006;Rajasekhar et al 2015;Viet et al 2011) have been reported to interfere with the amyloid aggregation of associated proteins. Few investigations Abstract Here, we have strategically synthesized stable gold (AuNPs Tyr , AuNPs Trp ) and silver (AgNPs Tyr ) nanoparticles which are surface functionalized with either tyrosine or tryptophan residues and have examined their potential to inhibit amyloid aggregation of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…20 In our lab, we study the modulation of aggrephagy using small molecules in yeast model. One such protein is α-synuclein which is intrinsically disordered and involved in Parkinson's disease pathogenesis.…”
Section: Monitoring the Clearance Of Mis-folded Protein Aggregates Inmentioning
confidence: 99%